Survey on anonymous authentication mechanisms of VANET - Tian-han GAO; Yan-qiang LI (网络与信息安全学报)
VANET has an attractive prospect,it faces serious security issues but at the same time.Access authentica-tion and privacy protection will play important roles to address the issues.A detailed survey on the literature anonymous authentication mechanisms of VANET in terms of their implementation approaches were presented such as anonymous credential and digital signature.The advantages and disadvantages of each mechanism were elabo-rated and the novel research directions were also given with the help of analysis.